2021
DOI: 10.1007/s40121-021-00423-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Antibody Responses in Patients with Different Severity of COVID-19: A Retrospective Study

Abstract: Introduction The coronavirus disease 2019 (COVID-19) pandemic is a serious public health event and poses a global health threat. To study the specific antibody responses would contribute to a better understanding of COVID-19. Methods We collected complete follow-up data from 777 patients with pathogen-confirmed COVID-19 with corresponding immunoglobulin G and M (IgG/IgM) testing results. Results Overall, the positive rates of IgG and IgM in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“… 7 , 8 , 9 Previous studies suggested that patients with COVID‐19 differ from the infection levels often leading to different outcomes of treatment. 39 While no significant decrease in ACM was found between SOC and 14 other medications or placebo for severe COVID‐19 infection. This result seems to be inconsistent with prior NMA studies by Zhang et al, 40 Wu et al, 41 and Siemieniuk et al 42 They suggested that tocilizumab or corticosteroids might reduce the ACM compared with SOC for COVID‐19 infection.…”
Section: Discussionmentioning
confidence: 95%
“… 7 , 8 , 9 Previous studies suggested that patients with COVID‐19 differ from the infection levels often leading to different outcomes of treatment. 39 While no significant decrease in ACM was found between SOC and 14 other medications or placebo for severe COVID‐19 infection. This result seems to be inconsistent with prior NMA studies by Zhang et al, 40 Wu et al, 41 and Siemieniuk et al 42 They suggested that tocilizumab or corticosteroids might reduce the ACM compared with SOC for COVID‐19 infection.…”
Section: Discussionmentioning
confidence: 95%
“…In regard to RT-PCR and antigen testing, although the number of studies is limited, it has been reported that the viral load in upper respiratory tract specimens measured using the RT-PCR test or antigen tests is associated with the severity of COVID-19 ( Fajnzylber et al, 2020 ). In regard to antibody tests, while some studies contend that the titers of antibodies against SARS-CoV-2 do not show positive associations with the disease severity ( Gozalbo-Rovira et al, 2020 ; Kong et al, 2020 ; Phipps et al, 2020 ), numerous other studies have demonstrated the existence of associations between SARS-CoV-2 antibody titers and the severity of COVID-19 ( Röltgen et al, 2020 ; Bläckberg et al, 2021 ; De Donno et al, 2021 ; Fu et al, 2021 ; Legros et al, 2021 ; Lu et al, 2021 ; Patil et al, 2021 ; Shrivastava et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, others have reported data indicating that the earlier appearance of IgM and IgG and also higher titres are associated with delayed viral clearance and increased disease severity. [27][28][29] Liu and colleagues found that IgM titre changes as COVID19 progresses and that high levels of IgM were associated with a higher risk of clinical adverse events. 30 However, others have reported that a robust IgG response and also detection of IgA in early disease correlated with a critical illness.…”
Section: Discussionmentioning
confidence: 99%